Analisis Kelayakan Usaha Budidaya Udang Vanname (Litopenaeus vannamei) di Keramba Jaring Apung Laut - Witoko, Pindo; Purbosari, Ninik; Noor, Nuning Mahmudah (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
Pacific white shrimp is one of the primadona of fishery commodities. The development of Pacific white shrimp can be done by using floating net cage (FNC). Shrimp culture in sea floating net cage is the one of alternative aquaculture of environmentally friendly shrimp cultivation and potentially become applicative technology of shrimp farming in the future. The aims of this study were to know the feasibility of white shrimp culture in sea floating net cage. The study was conducted by using descriptive and analytic method with 18 pieces of cage. Analysis of the feasibility using net present Value (NPV),Internal Rate of return (IRR), Net Benefit-Cost Ratio, Gross Benefit-Cost Ratio, Payback Period (PBP), and Break Even Point (BEP). The study result show that the NPV is IDR 43,315,360.00; IRR is 21.47%; net B/C ratio is 5.11, gross B/C ratio is 3.71; PBP is 6 months and 9 days and BEP is 1,837.82 kg of shrimp biomass or IDR 147,025,891.18 of the value of sales. The final result of feasibility analysis of shrimp culture in sea floating net cage is feasible to run.